The Toxic and Pathophysiological Aspects of Smoking Related to the Most Usual Forms of Use and Exposure to Tobacco Smoke – A Systematic Review - de Jesus Mariano Lacerda, Isadora; Eloise Domingues, Cinthia (Orbital: The Electronic Journal of Chemistry, 2025)
This review aimed to delineate the toxicity and pathogenicity of conventional, electronic, and hookah cigarettes concerning active and passive smoking, bringing epidemiological aspects related to Brazil. The research, conducted on the descriptors "nicotine extraction", "nicotine and toxicology", and "smoking and pathophysiology" in the Science Direct, Pubmed, Scopus, and Web of Science databases, resulted in the selection of 28 articles (2010-2022). Outside, also, exposed by the IBGE System of Automatic Recovery (SIDRA) in association with the National Health Survey (PNS), the percentages related to national smoking. It was found that the main affected systems are immunological, respiratory, and cardiovascular, with occurrences of cytotoxicity and genotoxicity, factors that are associated mainly with the presence of nicotine and toxic metabolites in cigarette smoke. It was also shown that levels of heavy metals can be found in e-cigarettes and that hookah. Conventional cigarettes still are the most harmful form of smoking. It is seen that indirect smoke stands for a serious public health problem because 80% of nitrosamines deposited on surfaces are not removed under normal ventilation conditions. It is concluded that smoking, regardless of the form of exposure, is harmful to the biological system, directly and indirectly affecting essential organs for human survival.